AKUISISI BAHASA DAN PREFERENSI BAHASA ASING DALAM SUDUT PANDANG SOSIOLINGUISTIK - I Made Suardika Jaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
In the realm of sociolinguistics, the acquisition of language is one of the important stages in one's linguistic level. Determination of which language is a person's mother tongue is determined in this phase. After going through several advanced phases, one will know various other languages. After learning certain languages in his life, a person will find that there are languages that he does not understand or has never learned before. This language can then be referred to as a foreign language. Foreign languages are very crucial to comprehend according to needs and interests. Foreign languages do not only refer to languages from other countries, but also languages from other regions within a country that are not understood by certain speakers. Foreign language preferences will facilitate the learning process as a linguistic provision that can increase competence to be able to face the era of the industrial revolution 4.0.Key words: sociolinguistics, language acquisition, foreign language preference